2019
DOI: 10.1111/twec.12781
|View full text |Cite
|
Sign up to set email alerts
|

Labour market characteristics and surviving import shocks

Abstract: This paper investigates whether different labour market characteristics amplify or dampen the local labour market impacts from Chinese import competition exposure. I exploit state‐level variation in initial, pre‐shock labour market characteristics and regional variation across local labour markets in exposure to Chinese imports for identification. I find that local labour markets in states with higher union density experience more severe adverse consequences as a result of increased import exposure. Conversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…For example, Autor et al (2020) illustrate that the regions in the United States exposed to significant Chinese import penetration experience more political polarisation, which is measured by public support for politically extremist candidates. More recent evidence given by Chan (2019) shows the Chinese import penetration increases the rate of unemployment, which can surge political polarisation. Colantone and Stanig (2018) also observe that the number of votes for "Leave" in the Brexit referendum was higher in cities, which are "hit harder" by the outcomes of globalisation.…”
mentioning
confidence: 99%
“…For example, Autor et al (2020) illustrate that the regions in the United States exposed to significant Chinese import penetration experience more political polarisation, which is measured by public support for politically extremist candidates. More recent evidence given by Chan (2019) shows the Chinese import penetration increases the rate of unemployment, which can surge political polarisation. Colantone and Stanig (2018) also observe that the number of votes for "Leave" in the Brexit referendum was higher in cities, which are "hit harder" by the outcomes of globalisation.…”
mentioning
confidence: 99%
“…In a related vein, Bernard, Jensen, and Schott (2006) showed that increased exposure to import competition from China leads to lower probability of plant survival and to a sharp decrease in plant employment and output growth in the United States. Chan (2017) found that the effects of Chinese imports differ across US states with distinct labor-market characteristics such as union density and minimum wages.…”
Section: Literaturementioning
confidence: 99%
“…Later on, we will show that the economy features a steady state (instead of a balanced growth path) due to the obsolescence of products. 11 The steady-state value of an invention is:…”
Section: Domestic Capital Goodsmentioning
confidence: 99%
“…A firm may own the patents for producing multiple varieties of domestic capital goods 11. See alsoGrossman and Lai (2004) 12.…”
mentioning
confidence: 99%
See 1 more Smart Citation